2023
DOI: 10.31219/osf.io/rn93w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The value of sign and print: Language proficiency predicts deaf signers’ occupational prestige and income

Abstract: Deaf bilinguals' language proficiency, job prestige and earnings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In addition, we generated the following independent variables: IQ, risk aversion, education (high; low), patience (time preference), financial knowledge, self-control, saving intention and financial future time perspective (live_for_present). As people's temporal values may influence their financial well-being (see Zheng et al, 2023), we generated a Temporal-focus Index (TFI) for each participant, TFI = (mean of future-focused itemsmean of past-focused items)/(mean of future-focused items + mean of past-focused items) (de la Fuente et al, 2014). Moreover, we control for demographic factors children number, gender (male1), age, partner, generation2, and education (highedu1).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we generated the following independent variables: IQ, risk aversion, education (high; low), patience (time preference), financial knowledge, self-control, saving intention and financial future time perspective (live_for_present). As people's temporal values may influence their financial well-being (see Zheng et al, 2023), we generated a Temporal-focus Index (TFI) for each participant, TFI = (mean of future-focused itemsmean of past-focused items)/(mean of future-focused items + mean of past-focused items) (de la Fuente et al, 2014). Moreover, we control for demographic factors children number, gender (male1), age, partner, generation2, and education (highedu1).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Studies investigating the relationship between language proficiency and immigrants' labour market performance have shown that host-country language proficiency has an impact on employment possibilities and earnings. For example, researchers have found a relation between speaking and writing proficiency and immigrants' earnings in Germany (Dustmann, 1994), between language skills and employment possibility of immigrants in the UK (Dustmann & Fabbri, 2003), Italy (Luca et al, 2022), and Switzerland (Wong, 2022), between English proficiency, age of arrival, and earnings among US immigrants (Bleakley & Chin, 2004), and between sign language proficiency of Chinese deaf signers and their occupational prestige and income (Zheng, Lin & Gu, 2023). Recent studies also suggest that there is an effect of language proficiency on the gender wage gap (Miranda & Zhu, 2020), for example due to a negative effect of immigrants' language problems on females' hourly wages (Yao & van Ours, 2015).…”
Section: Introductionmentioning
confidence: 99%